Empirical Assessment of the Effect of Financial Reporting Components on Investment Decisions of Small and Medium Enterprises in Nigeria - Akinadewo, Israel Seriki; Al-Amen, Saliu; Dagunduro, Muyiwa Emmanuel; Akinadewo, Jeremiah O. (Archives of Business Research, 2023)
Financial reporting is a critical aspect of business operations that enables companies to communicate relevant financial information to their stakeholders. The primary goal of financial reporting is to provide investors with information that can assist them in making informed investment decisions. Therefore, this study aimed to investigate the effect of financial reporting on the investment decisions of SMEs. The study made use of primary data. Primary data was collected using an interview guide and questionnaires, with respondents being those in charge of making investment decisions in the firm under study or their agents. The questionnaire included both closed-ended and Likert-type questions. 150 questionnaires were administered out of which 100 were completed and returned. In order to ensure the reliability of the measures used in this research, the researcher conducted a random re-test exercise within the population sample of the study. The study findings indicate that financial reporting has a significant impact on the investment decisions of SMEs. The comprehensive income statement, statement of financial position, cash flow statement, and the statement of changes in shareholder's equity were found to have a significant positive effect on investment decisions. This finding implies that investors consider the information contained in these financial statements when making investment decisions. The study results state the importance of including all financial statements in financial reporting, as each statement provides unique information that can be relevant to investors. The study therefore recommended among other things; The Nigerian government and regulatory bodies should strive to improve financial reporting standards for SMEs, SMEs in Nigeria should be encouraged to undergo financial literacy education to improve their understanding of financial statements, the government should provide incentives such as tax breaks and subsidies to SMEs that prepare and disseminate comprehensive financial report.